+0  
 
0
30
1
avatar

https://web2.0calc.com/questions/quadratic_91694

 Jul 27, 2022
 #1
avatar+124524 
+1

Let a and b be the roots of the quadratic 2x^2 - 8x + 7 = x^2 - 5x + 3.  Compute a^3*b + a*b^3.

 

Note that

 

a^3b + ab^3  =  ab ( a^2 + b^2)

 

Rearrange  equation  as     x^2 - 3x  + 4  = 0

 

By Vieta

 

Sum of roots  = -(-3) /1  = 3     and product of roots  = 4/1 =  4

 

So

 

a + b  = 3     square both sides                            and             ab  = 4    so    2ab =  8

 

a^2  + 2ab + b^2 =  9

 

a^2 + b^2   =   9 - 2ab

 

a^2 + b^2  =  9  - 2(8) =    -7

 

So

 

a^3b + ab^3  =  ab ( a^2 + b^2) =   4 ( -7) =    -28

 

 

cool cool cool

 Jul 27, 2022
edited by CPhill  Jul 27, 2022

14 Online Users

avatar